A comparative study on vulcanization behavior of acrylonitrile-butadiene rubber reinforced with graphene oxide and reduced graphene oxide as fillers. (July 2019) - Mensah, Bismark; Gupta, Kailash Chandra; Kang, Gilyang; Lee, Harim; Nah, Changwoon
Abstract: A comparative study on vulcanization of acrylonitrile-butadiene rubber (NBR) has been carried out in presence of graphene oxide (GO) and reduced graphene oxide (rGO) nanosheets. This was to evaluate the role of structural stability, surface functionality and degree of dispersion of the nanosheets on curing and physico-mechanical properties of NBR-GO/rGO composites. The prepared nanocomposites were characterized for surface morphology, topology and dispersion of GO/rGO nanosheets using scanning electron microscopy (SEM), and atomic force microscopy (AFM) analyses. The mixing and interactions of GO/rGO nanosheets with NBR were confirmed by recording Fourier transform-infrared (FT-IR) spectra. An oscillating die rheometer (ODR) and a differential scanning calorimetry (DSC) have been used to evaluate the cure behavior of NBR-GO/rGO nanocomposites. The activation energy (Ea ) of curing for rGO nanosheets reinforced NBR composites was determined by Ozawa and Kissinger method, which was found to be lower than GO nanosheets reinforced NBR composites. This clearly suggested that rGO nanosheets promoted faster curing of NBR than GO nanosheets. The relative values of swelling (Qr /Qc ), swelling ratio (Qr ) and Young's modulus (E/MPa) of NBR-GO/rGO nanocomposites indicated higher cross-linking density in NBR-rGO nanocomposites owing to the better dispersion and effective curing rate index (CRI) of rGO nanosheets within NBR. The curing behavior of GO/rGO nanosheets reinforced nanocomposites was explained by proposing the schemes of curing in presence of curing agents and accelerators. These studies are likely to be useful to prepare NBR vulcanizates with tailored properties for high performance industrial applications and methods for characterization of NBR based vulcanizates. Highlights: This research article covers the curing aspect of polar rubber (NBR) in the presence of graphene oxide and graphenes. Characterization of their cure behaviors was carried out using cure rheometer, differential scanning calorimeter, and swelling method. The cure kinetics was analyzed by Ozawa and Kissinger models, and the result showed a faster curing reaction of graphene-NBR composites than graphene oxide-NBR composites. The additional formation of curing network was suggested either between graphenes and accelerated sulfur cure system or between acrylonitrile group in NBR and functionality of graphene surface.